2011
DOI: 10.2478/s11687-011-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Human dirofilariosis: The report of subcutaneous Dirofilaria repens infection in the Slovak Republic

Abstract: SummaryDirofilariosis is a vector-borne disease that is spreading in Europe from the southern endemic regions to the northern countries, including Slovakia. The dog parasites Dirofilaria immitis and D. repens are zoonotic agents, responsible for the development of human pulmonary and subcutaneous dirofilariosis, respectively. The present paper reports the third case of human dirofilariosis in Slovakia caused by D. repens. The pacient, a 41-year-old woman, was referred with tumour process in the subcutaneous ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Canine dirofilariosis was also confirmed in neighbouring countries. In the second case (described by Ondriska et al, 2010) an intact worm of D. repens was isolated from a nodule on the forearm, whereas diagnosis of the first (Babál et al, 2008) and the third (Nováková et al, 2011) human cases was based on histological examination of excised tissues containing a worm. Shortly after detecting D. repens in dogs in Slovakia, the first autochthonous human case of subcutaneous infection was recorded by Babál et al (2008) in the same territory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine dirofilariosis was also confirmed in neighbouring countries. In the second case (described by Ondriska et al, 2010) an intact worm of D. repens was isolated from a nodule on the forearm, whereas diagnosis of the first (Babál et al, 2008) and the third (Nováková et al, 2011) human cases was based on histological examination of excised tissues containing a worm. Shortly after detecting D. repens in dogs in Slovakia, the first autochthonous human case of subcutaneous infection was recorded by Babál et al (2008) in the same territory.…”
Section: Introductionmentioning
confidence: 99%
“…In Slovakia, three human cases of D. repens have been recorded so far, and in the present paper we report a fourth case. In the second case (described by Ondriska et al , 2010) an intact worm of D. repens was isolated from a nodule on the forearm, whereas diagnosis of the first (Babál et al , 2008) and the third (Nováková et al , 2011) human cases was based on histological examination of excised tissues containing a worm.…”
Section: Introductionmentioning
confidence: 99%
“…The first diagnosed autochthonous canine dirofilariosis in Slovakia was caused by D. repens in 2005 (Svobodová et al, 2005), and in 2007 the first case of human subcutaneous dirofilariosis was identified in the patient from western Slovakia, who has never travelled abroad (Babál et al, 2008). Since the year 2007, 4 cases of human subcutaneous dirofilariosis caused by D. repens in Slovakia have been reported in total (Babál et al, 2008;Ondriska et al, 2010;Nováková et al, 2011;Hrčková et al, 2013). In Europe, the higher number of cases represented subcutaneous form, where cysts were frequently localized on head and around the eyes in comparison with the ocular form, when parasite was found in subconjuntival space of eye.…”
Section: Introductionmentioning
confidence: 99%